2002
DOI: 10.1007/s11892-002-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dietary fat on insulin resistance

Abstract: Dietary fat has been implicated in the development of insulin resistance in both animals and humans. Most, although not all, studies suggest that higher levels of total fat in the diet result in greater whole-body insulin resistance. Although, in practice, obesity may complicate the relationship between fat intake and insulin resistance, clinical trials demonstrate that high levels of dietary fat can impair insulin sensitivity independent of body weight changes. In addition, it appears that different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 47 publications
3
74
0
3
Order By: Relevance
“…A protective effect of lactose on glucose metabolism was expected, because dietary lactose elicits a relatively low glycemic response in clinical studies (34). The adverse effect on insulin sensitivity may, however, be a result of the relationship between milk products and lactose, because milk and dairy products comprise not only lactose but also saturated fat, which is strongly associated with increased insulin resistance (35,36). Adjustment for saturated fat did not, however, change the observed significant association between lactose and HOMA-IR in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A protective effect of lactose on glucose metabolism was expected, because dietary lactose elicits a relatively low glycemic response in clinical studies (34). The adverse effect on insulin sensitivity may, however, be a result of the relationship between milk products and lactose, because milk and dairy products comprise not only lactose but also saturated fat, which is strongly associated with increased insulin resistance (35,36). Adjustment for saturated fat did not, however, change the observed significant association between lactose and HOMA-IR in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Oleic acid is the most abundant fatty acid in nature and is present in almost all vegetable oils and fats. Oleic acid is gaining importance in human nutrition owing to its potential health benefits against cardiovascular heart diseases and its cholesterol lowering effects (Kris-Etherton 1999;Lovejoy 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In the muscle, overall differences in SFA, MUFA, and PUFA between groups were not significant ( Excessive SFA and high MUFA can cause an energy imbalance and weight gain within the body, inducing insulin resistance and other nutritional diseases. PUFA, particularly n-3 PUFA, can eliminate this resistance (Lovejoy, 2012). Therefore, we set SFA + MUFA + PUFA = 100 scores, and the SFA, MUFA, and PUFA were averaged of 33.33 each for a standard ratio of 1:1:1.…”
Section: Sfa:mufa:pufa Comparisonmentioning
confidence: 99%
“…By analyzing the hepatopancreas, gonad, and muscle fatty acid composition of Yangcheng Lake river Eriocheir sinensis (Chen and Zhang, 2007), female Yangcheng lake and pool Eriocheir sinensis (Kong et al, 2012), Portunus pelagicus (Wu et al, 2010), Carcinus mediterraneus (Cherif et al, 2008), Callinectes sapidus (Çelik et al, 2004), and Paralithodes and Chionoecetes (Latyshev et al, 2009), the results show that the relative mass of fat differed in different species, different origin, and different breeding patterns (Table 4). High MUFA caused an energy imbalance of the inner environment (Lovejoy, 2012); a high intake of C18:2 and low intake of MUFA were associated with the incidence of breast cancer (Goodstine, 2003). DHA and EPA can lower blood pressure and have antithrombotic and antitumor effects, as well as prevent heart disease and improve physiological functions.…”
Section: C16:1 C18:2 Epa and Dha Comparisonmentioning
confidence: 99%